E-Government in Zimbabwe: An overview of progress made and challenges ahead - Naome Rajah (Research and Reviews, 2023)
This paper surveyed the level of preparedness by the Zimbabwe government in using information and communication technologies to enhance the range and quality of services provided to the citizen; and determined the extent of, and continuous improvement efforts of Zimbabwe leaders towards the attainment of connected government. Data for the study was a secondary data adapted from the Internet. The UN global e-government readiness ranking and the models of e-government were downloaded, adapted and used as a benchmark for measuring the web readiness of the Zimbabwe governments in 2005, 2008, 2010 and 2012. It was discovered that the Zimbabwean government has demonstrated its willingness to apply information and communication technologies (ICTs) in their public administration, but is at the emerging stages. A serious impediment which characterized e-government readiness in Zimbabwe is low level of human capital and knowledge economy. The implications include poor provision of government services and underutilization of ICTs facilities in Zimbabwe which might result in the widening of ‘access divide’ between the rich and the poor.